Socially inclusive digital tools for agriculture: A way forward - Dittmer, Kyle M.; Wollenberg, Eva Karoline; Burns, Sessie A. (Bioversity International and the International Center for Tropical Agriculture, 2022)
KEY MESSAGES ◼ Socially inclusive digital tools are necessary to support diverse smallholder farmers’ access to digital services such as technical advice and access to markets. Improving smallholders’ access to digital resources and providing tool functions and features that enhance social inclusion are both necessary. ◼ Tool features that enable two-way communication, multiple channels of communication, co-creation of practices, and farmers’ demonstration plots support more inclusive technical advisory services. ◼ Performance assessment tools can support smallholder inclusion by assuring that farmers retain ownership of personal and assessment data, that data are stored privately and securely within each user account and that farmer data are not being used for the profit of the tool developer or implementor. ◼ Mobile learning applications, gamification, SMS-alerts, and chatbots within digital tools make learning about agricultural insurance accessible to smallholders and improve adoption. ◼ Digital tools that promote the aggregation of smallholder products or serve as an e-commerce platform allow smallholders to fairly engage in formal markets. ◼ Principles for inclusion can help guide digital tool design and use.